Nutritional Habits' Review of Amateur and Professional Football Players - Fatma Nur Türkoğlu; Orhan Şener; Ahmet Çöndü (Selcuk University, 2019)
ABSTRACT The aim of our study is to investigate the dietary habits of amateur and professional football players and their differences.A hundred football players actively playing football during the 2013-2014 football season in 2nd League A Category, 2nd League B Category, 3rd League, 1st Amateur and 2nd Amateur Leagues participated in our study.  A questionnaire that consists of 17 personal information and nutritional habits questions was developed based on the literature and was filled out by the players to determine their nutritional habits. There were statistically significant differences between the groups at p lt;0.01 level across their education level on nutrition issues, number of meals, alcohol and cigarette use, daily fluid intake, pre-game fluid intake, pre-game foods consumed, liquids and food consumed outside of three regular meals, late-time meals, regular supplementary products and last food before games. There were statistically significant differences between the groups at p lt;0.05 level across information resource on nutrition issues, skipped meals, fluid intake during training, late time meals, attention to expiration dates while shopping.In conclusion, consistent with previous studies in the literature it is found that amateur and professional football players don't have good nutrition information and habits. Clubs, coaches and athletes looking for success on a national and international level should consult and collaborate with a nutritionist. We believe that it will be very useful to train athletes and coaches, with seminars, courses, panels, etc. and to have an expert dietitian in sports clubs, and to emphasize the importance of this issue in written and visual media.